Treatment-resistant manic episode in a patient diagnosed with bipolar affective disorder. (20th October 2022) - Papadimitriou, Nikolaos; Antoniadis, Diomidis; Ververi, Athina
Abstract : A considerable group of patients suffering from mental health disorders do not respond adequately to pharmacological treatment. For the purposes of precision and personalized medicine, pharmacogenomics has been developed as a valuable and promising tool. The technology of identifying single nucleotide polymorphisms and genotyping supplies clinicians, and therefore their patients, with the opportunity of avoiding long-lasting 'trial and error' periods, reducing the risk of manifesting disturbing adverse effects during treatment. Consequently, better adherence to treatment and clinical response can be achieved, contributing to personalized treatment planning, according to a person's genetic profile and needs. In the present report, we present a case of an individual diagnosed with bipolar affective disorder type I, who showed resistance to pharmacological treatment and underwent through pharmacogenomic investigations, in order to identify the appropriate medication for the best possible clinical response.